A lower bound on the number of finite simple groups - Michael E. Mays (International Journal of Mathematics and Mathematical Sciences)
Let S(n)=|{m<n: there is a (non-cyclic) simple group of order m}|. Investigation of known families of simple groups provides the lower bound S(n)≫n1/4/logn.